Our experience with Amyand’s hernia - Gupta, Brajesh; Hatwar, Ghanshyam; Tiwari, Charu; Gupta, Shweta (International Surgery Journal, 2019)
Amyand’s hernia is a rare type of inguinal hernia with appendix as its content, which may be normal or pathological. We present our experience with Amyand’s hernia in 6 patients. A retrospective review of 6 cases with Amyand’s hernia that were managed over a 2-year period was done by reviewing the hospital records. The variables assessed and analyzed were demographic details, clinical presentation, management and follow-up. There were 4 children and 2 adults; male and female ratio being 5:1. The mean age of four children was 1.5 years; the two adults were 72 and 54 years of age. The duration of symptoms of inguinal hernia ranged from 1 month to one year; mean duration of irreducibility was 5.33 days (range: 2 days to 15 days). Five patients had symptoms of obstruction. All 5 patients with obstruction underwent emergency surgery. The sixth patient was posted for elective hernioplasty the next day. Appendix was inflamed only in one patient. The post-operative course was uneventful in all patients. The mean duration of hospital stay was 3.33 days. Only one patient had surgical site infection. Amyand’s hernia, thus presents with features of incarcerated right hernia. Pre-operative diagnosis is difficult. Intra-operatively, the surgical procedure needs to be individualized depending upon the pathology.